Teachers’ Leadership and Students’ Motivation to Learn English - Rizqi Khoirunnisa; Utami Widiati (Graduate School of Universitas Negeri Malang, 2020)
Abstract: Teacher leadership is a leadership attitude shown by the teachers involving idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This study is conducted to investigate the relationship between teacher leadership and students’ motivation to learn English. By knowing the association between these variables, English teachers will be able to strategize in conducting the learning process in class to motivate their students. If students are motivated in learning English, then their performance and achievement might increase too. The design of the study is correlational. The relationship is determined by correlating scores from two questionnaires given to the students. The result indicated that there is a positive moderate relationship between teacher leadership and students’ motivation in learning English. The correlation coefficient is 0.342. It means that the higher the degree of teachers’ leadership, the higher the students’ motivation. In contrast, when the teachers have low degree of leadership, the students will gradually lose their motivation. In conclusion, the result of this study has shown that there is a significant relation between teachers’ leadership and students’ motivation.Abstrak: Kepemimpinan seorang guru dalam melakukan pembelajaran di dalam kelas dapat dilihat melalui beberapa hal, yaitu idealized influence, inspirational motivation, intellectual stimulation, dan individualized consideration. Penelitian ini dilakukan untuk menginvestigasi hubungan antara kepemimpinan guru dengan motivasi siswa dalam belajar Bahasa Inggris. Dengan mengetahui hubungan antar dua variabel ini, guru dapat mengatur strategi lebih baik dalam melakukan proses belajar di kelas. Hasil penelitian mengindikasikan adanya hubungan positif yang sedang antara kepemimpinan guru dengan motivasi siswa dalam belajar bahasa Inggris. Koefisien korelasinya adalah 0.342. Hal ini berarti semakin tinggi kualitas kepemimpinan guru, semakin baik pula motivasi siswa dalam mempelajari Bahasa Inggris. Begitu pula jika guru mempunyai kualitas kepemimpinan yang rendah, maka besar kemungkinan bahwa lambat laun siswa akan kehilangan motivasi dalam belajar Bahasa Inggris. Kesimpulannya, kepemimpinan guru mempunyai hubungan yang signifikan dengan motivasi siswa dalam belajar bahasa Inggris.